SOSIALISASI PENGUATAN MOTIVASI BELAJAR UNTUK MENCETAK GENERASI UNGGUL DI SMK NURUL HUDA BAROS - Haryono, Riki; Winaldo, Jepri; Octaviani, Rani; Febrianti, Empin; Setiawan, Farhan Nanda (BESIRU : Jurnal Pengabdian Masyarakat, 2025)
Community service is one of the tangible manifestations of the role of universities in making a positive contribution to the surrounding environment. One of the important aspects of human resource development is learning motivation, because motivation plays a big role in determining the achievements and readiness of the younger generation to face future challenges. This program carries the activity "Socialization of Strengthening Learning Motivation to Produce a Superior Generation at SMK Nurul Huda Baros", which is located on Jl. Raya Pandeglang Km 14, Kampungsawah, Baros, Sukamanah, Serang, Serang Regency, Banten 42173. The implementation method is carried out through socialization activities with a participatory approach, in the form of delivering materials, interactive discussions, and simple simulations on how to maintain and increase learning motivation. The material covers the basic concepts of motivation, the factors that affect motivation, as well as practical steps such as time management, goal setting, and strengthening the growth mindset. With this method, students gain not only knowledge, but also hands-on experience in understanding the importance of motivation for their future.